2015
DOI: 10.1590/s0080-623420150000600005
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of cardiopulmonary resuscitation in inpatient units: perception of nurses

Abstract: Objective: To identify, in the perception of nurses, the factors that affect the quality of cardiopulmonary resuscitation (CPR) in adult inpatient units, and investigate the influence of both work shifts and professional experience length of time in the perception of these factors. Method: A descriptive, exploratory study conducted at a hospital specialized in cardiology and pneumology with the application of a questionnaire to 49 nurses working in inpatient units. Results: The majority of nurses reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 17 publications
2
20
1
11
Order By: Relevance
“…Although the shortage of human resources and fatigue of therapists in the night shift affects the delivery of optimal services and have been addressed previously, no data was found on the association between working shift and the success of CPR and the quality of services (26,27). Contrary to expectations, the current study finds a significant difference between CPR success rate and work shifts although, some studies have reported a relationship between long working hours and reverse outcomes in health care (28,29).…”
Section: Discussioncontrasting
confidence: 83%
“…Although the shortage of human resources and fatigue of therapists in the night shift affects the delivery of optimal services and have been addressed previously, no data was found on the association between working shift and the success of CPR and the quality of services (26,27). Contrary to expectations, the current study finds a significant difference between CPR success rate and work shifts although, some studies have reported a relationship between long working hours and reverse outcomes in health care (28,29).…”
Section: Discussioncontrasting
confidence: 83%
“…O estudo realizado no Instituto mostra que a presença de um líder melhora a qualidade da assistência. No entanto essa presença não é importante apenas no momento da assistência à PCR, mas também para dividir as atribuições entre sua equipe de acordo com suas competências legais, tornando-os corresponsáveis pela assistência (Filho, Santos, Silva & Nogueira, 2015).…”
Section: Discussionunclassified
“…O estudo no Instituto demonstra que enfermeiros com maior tempo de experiência profissional apontam que os aspectos que interferem na qualidade da RCP são a falta de relação harmoniosa da equipe, de material e/ou falha de equipamento durante o atendimento e de familiarização com o carrinho de PCR. E, reafirma que a falta da presença de um líder, ou a presença de um familiar durante a RCP, bem como o estresse de algum membro da equipe influenciam a qualidade do atendimento (Filho, Santos, Silva & Nogueira, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The unit was intentionally chosen due to the high need of using the emergency car in relation to the other hospitalization units, in which the patients have greater clinical stability. 15 The unit has two emergency cars.…”
Section: Methodsmentioning
confidence: 99%